Mechanically durable thermoelectric power generation module made of Ni-based alloy as a reference for reliable testing. (15th February 2020) - Chetty, Raju; Nagase, Kazuo; Aihara, Makoto; Jood, Priyanka; Takazawa, Hiroyuki; Ohta, Michihiro; Yamamoto, Atsushi
Graphical abstract: Highlights: We develop a thermoelectric module made of Ni-based alloys as a standard reference. Ni90 Cr10 and Cu55 Ni45 are used in p-type and n-type legs, respectively. Module developed in this study is chemically, thermally and mechanically stable. Power generation characteristics are reproducible in repeated and continuous tests. Abstract: In this study, we fabricated a thermoelectric module made of Ni-based alloy as standard reference for use in cross-checking the power generation characteristics of module testing systems. The module was fabricated with eight pairs of legs made from mechanically durable p-type Ni90 Cr10 (chromel) and n-type Cu55 Ni45 (constantan). To increase thermal resistance of the module, holes were made in the p- and n-type Ni-based alloys, thereby reducing the effective density of the legs by 57.1%. As a result, a thermal resistance of 6.16 K W −1 was obtained at a hot-side temperature ( T h ) of 773 K and cold-side temperature ( T c ) of 323 K. A maximum electrical power ( P max ) of 0.39 W and maximum conversion efficiency ( η max ) of 0.53% were obtained for the module with holes at T h of 773 K and T c of 323 K. We confirmed the reproducibility of power generation characteristics, including the open circuit voltage ( V oc ), internal resistance ( R in ), P max, output heat flow ( Q out ), and η max of the module, through 12 repeated tests and 120 h of continuous tests at T h of 773 K and T c of 323 K. The variation of V oc, R in, P max, Q out, and η max is with standard deviation less than 1% from their mean values.